EFEKTIVITAS KEBIJAKAN PENGEMBANGAN PARIWISATA DALAM MENUNJANG PEMBANGUNAN DAERAH DI KABUPATEN TOLITOLI PROVINSI SULAWESI TENGAH. - Walangitan, Stephani Fransisca (Sam Ratulangi University, 2014)
ABSTRACT :Walangitan , Stephani F , The effectiveness of tourism policies in supporting regional development of Toli Toli Regency in Central Sulawesi Province . Thesis of Faculty of Social and Political Sciences, Sam Ratulangi University. Supervisors by : ( 1 ) Drs.J.Mandey , M.Sc. ( 2 ) Drs.S.P.I. Rompas , M.Sc.The problem that face by most of local governments in Indonesia is the implementation of autonomous government without being overly dependent to the central government. It seems that this challenge of implementation is not simple to deal with by the local government. This condition is reflected in the high level of demand of GAF ( General Allocation Fund) from most of the local government to the central government .Relevant to the feature and characteristics of the problems examined, this research is used descriptive - analytical method ( Nazir , 1988 ; Koentjaraningrat , 1997) . Descriptive methods can be interpreted as a process of solving problems examined by describing the current subject and object of the research based on the facts that appear or how is it appear ( Nawawi , 2003) . To examine the effectiveness of tourism development policies in Toli - Toli . To analyze the policies contribution to the success of tourism development policy towards regional development, particularly in Toli – Toli region. For identifying and assessing the barriers faced by local governments of Toli - Toli in implementation of tourism development policy in this area.Based on the results of data retrieval in that taking from the Department of Tourism in Tolitoli, Central Sulawesi, The existing data shown that there are 36 tourism objects in that area that consists of natural attractions, cultures, and history but only 2 tourism objects that managed by the government in this case, Department of Tourism and the rest remaining objects managed by the local community.As a suggestion, It is better if the Department of Tourism can collaborate and working together with the local community in the development and management of tourism in Toli-Toli region, Central Sulawesi Province to increase the potential tourist attraction in order to increase local exchange and public welfare.Keywords : the development of tourist attraction , society welfare , local exchange.